Perancangan Buku Cerita Bergambar Tentang Bullying Pada Anak - anak Berjudul Sepeda Tua Dan Semangat Si Made Dengan Teknologi Augmented Reality Kolaborasi Karakter Blelozz di Madeblez Studio - Hendra, I Made; Artawan, Cokorda Alit; Negara, I Nengah Sudika (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
Bullying is a negative behavior carried out by a stronger party against a weaker one, using or not using tools, with the aim of causing them to feel pressured, both physically and emotionally (M. Miftahuddin Al Amin, 2018:12). Bullying behavior has become a common occurrence among children, resulting in long-term psychological impacts on individuals. There is a need for a medium that can be used to educate about the effects of bullying and how to cope with it. The illustrated storybook "Old Bike and Si Made's Spirit" addresses this topic to showcase the impact of bullying and how to confront it, based on the author's own experiences as a victim during childhood and adolescence. The story revolves around Made, who comes from an underprivileged family and becomes the subject of ridicule by peers. Despite this, Made competes in a cycling championship, demonstrating his abilities to everyone. The research method used to obtain the necessary data is qualitative research through interviews, participant, observation, documentation, and literature review. The result of this project is an A4-sized illustrated storybook with 15 scenes, incorporating Augmented Reality technology on its cover.